If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + -2 = 58 Reorder the terms: -2 + 12x = 58 Solving -2 + 12x = 58 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 12x = 58 + 2 Combine like terms: -2 + 2 = 0 0 + 12x = 58 + 2 12x = 58 + 2 Combine like terms: 58 + 2 = 60 12x = 60 Divide each side by '12'. x = 5 Simplifying x = 5
| (2x-3)/5+4=x-2 | | 13+(-12)-(-5)=? | | 4x-6=-122 | | 2(y+4)=26 | | 2(y+5)=26 | | 3-2=13 | | 7-5x=7+3x | | f-13+7=2 | | 3(y+7)=36 | | 12-1=4p+23 | | a^3+2a^2-25a-50= | | 2(y+6)=24 | | x+10=4x+1 | | -282-(+1,017)=? | | 2y+48=8 | | M^2-6=5m | | f(x)=25x+150 | | 141-6x=30x+21 | | 28+2x=6x | | 10x+4=29 | | -4.9t^2+19.6t+58.8=0 | | 6(y-5)=-6 | | 5(y+3)=55 | | b^2-4*b+4=0 | | 8x-32=18+6x | | 2x+8-4x-15=16+8x-2-3 | | (3x+6)= | | y=(3x/12)+105 | | 2(x-6)+3x=8 | | 3x+30=90 | | (x^2+2x+1)(x^2+5x+4)=0 | | y=3x/12+105 |